SUPERVISI AKADEMIK PEMBELAJARAN IPA MELALUI ICT BASED LESSON STUDY UNTUK MEMBANGUN LEARNING COMMUNITY GURU SD - Samsudin, Achmad (Universitas Pendidikan Indonesia, 2014)
Have conducted a study on academic supervision science learning through ICT based Lesson Study to develop a learning community for science teachers. This article was a written idea can be realized in learning science especially in elementary school. A community of learning among elementary science teachers needs to be developed in order to improve the quality of science teaching and student learning achievement in the schools. This idea is carried through descriptive method based on a literature review. Supervision programs are assessed and analyzed using a pattern of lesson study, combined with ICT based that can bridge between science teachers and lecturers in the schools are separated by distance and geographical location are difficult to reach and require large additional costs. Some advantages of academic supervision program of learning science through ICT based Lesson Study is to provide broad access to learning for among components such as science teachers, supervisors, principals and lecturers.Keywords: supervision of academic, science, ICT based Lesson Study, learning community.